UTILIZATION OF INSTAGRAM AS INFORMATION MEDIA IN SUPPORTING THE ACTIVITIES OF IBNU AQIL ISLAMIC BOARDING SCHOOL MEDAN - Ja'far; Walisyah, Tengku (Moestopo International Review on Social, Humanities, and Sciences, 2024)
This study investigates the use of Instagram by the Ibnu Aqil Islamic Boarding School in Medan (Pondok Pesantren Tahfiz Ibnu Aqil Medan). Data was collected through interviews, observations, and documentation. Interviews were conducted with the school's head, admin/media team, guardians of students, and students. Observations were made of the school's use of Instagram on the @ponpesibnuaqil account. Documentation included screenshots of posts and literature related to the study. The results showed that the Instagram account, with 2,062 followers, effectively disseminates information about the school's latest programs, activities, and information. The content includes documentation of activities, student achievements, announcements, and creative videos. The admin and media team, including students and educators, manage the content creation process. Instagram not only improves communication and interaction with the public or followers but also promotes Islamic boarding schools, builds personal branding, and collaborates with other institutions. In conclusion, Instagram's use as an information media by the school is effective in supporting various activities and achieving informative goals.